Chronic heat stress affects muscle hypertrophy, muscle protein synthesis and uptake of amino acid in broilers via insulin like growth factor-mammalian target of rapamycin signal pathway. (3rd July 2018) - Ma, Bingbing; He, Xiaofang; Lu, Zhuang; Zhang, Lin; Li, Jiaolong; Jiang, Yun; Zhou, Guanghong; Gao, Feng
ABSTRACT: Heat stress markedly impairs the growth performance of broilers, such as the reduction of breast muscle mass and yield. The aim of this study was to examine the molecular mechanism of depressed muscle mass and yield caused by heat stress. A total of 144 (28-day-old) male broilers were allocated randomly into 3 treatment groups: (1) the normal control group (environment temperature was 22°C), (2) the heat stress group (environment temperature was 32°C), (3) the pair-fed group (environment temperature was 22°C and pair-fed to heat stress group). The experiment lasted for 14 d (from the age of 28 to 42 d). After 14 d of heat exposure, heat stress decreased ( P < 0.05) broiler average daily gain, breast muscle mass, and muscle yield, and increased ( P < 0.05) feed to gain ratio. After 14 d of heat exposure, heat stress increased ( P < 0.05) the activities of aspartate aminotransferase and the concentrations of uric acid and most amino acids in serum, and reduced ( P < 0.05) the concentration of insulin like growth factor 1 (IGF-1 ) in serum. Additionally, heat stress decreased ( P < 0.05) the mRNA expressions of IGF-1, IGF-1 receptor, insulin receptor substrate 1, mammalian target of rapamycin (mTOR ), the 70 kD ribosomal protein S6 kinase, myogenic differentiation, myogenin, solute carrier family 38 member 2, solute carrier family 7 member 5, and solute carrier family 3 member 2 of the breast muscle. In conclusion, chronic heat stress resulted in lower breast muscle mass and yield, and decreased muscle protein synthesis and amino acid transportation by downregulating IGFs-mTOR signal pathway. These findings have important practical significance in discovering effective means to alleviate muscle loss caused by chronic heat stress.